Dukungan Suami Terhadap Psikologis Ibu Hamil Trimester III - Vebryana Eka Ayuningtyas; Karjiyem; Kurniasari Pratiwi (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background: A woman during pregnancy will experience changes both physically and psychologically. Atpresent the government's attention to pregnant women is still focused on physical health problems and lackof attention to mental health, even though in some countries as many as 1 in 5 women have mental healthproblems during pregnancy and in the first year after birth. More than 75% of women are not diagnosed, donot get adequate treatment and support so that it has important consequences for mothers, babies, familiesand society in general.Objective: To determine the partner support for the psychology of third trimester pregnant women.Research Methods: Type of research uses a qualitative descriptive method with a naturalistic approach.The population in the study were 20 married couples who were pregnant in the third trimester, while asample of 6 couples were pregnant women. The sampling technique was purposive sampling and thesampling method of this study was snowballing sampling.Research Results: The partner support is to pay attention to the nutrition of pregnant women, providemotivation, support, doing homework together, ensure a good pregnancy check-up, deliver health checks,ask questions about the wife's pregnancy health, paying attention and maintaining the health of the motherand fetus.Conclusion: Based on the results of the study it can be concluded that the support and participation of thehusband in pregnancy consists of informational support, assessment support, instrumental support, andemotional support.Keywords: Partner support, Psychology, Pregnant Women.